2010
DOI: 10.1007/s00778-010-0210-x
|View full text |Cite
|
Sign up to set email alerts
|

Resisting structural re-identification in anonymized social networks

Abstract: We identify privacy risks associated with releasing network data sets and provide an algorithm that mitigates those risks. A network consists of entities connected by links representing relations such as friendship, communication, or shared activity. Maintaining privacy when publishing networked data is uniquely challenging because an individual's network context can be used to identify them even if other identifying information is removed. In this paper, we quantify the privacy risks associated with three cla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
296
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(296 citation statements)
references
References 45 publications
0
296
0
Order By: Relevance
“…We require that the clustering algorithm returns a partition of the vertex set V of the graph and that each cluster or class of vertices contains at least k vertices. In [10], the authors use simulated annealing in order to find a partition of the vertices that satisfy k-anonymity and minimizes information loss, via a maximum likelihood approach. Heuristic methods are nice, because they work.…”
Section: A K-anonymization Algorithmmentioning
confidence: 99%
“…We require that the clustering algorithm returns a partition of the vertex set V of the graph and that each cluster or class of vertices contains at least k vertices. In [10], the authors use simulated annealing in order to find a partition of the vertices that satisfy k-anonymity and minimizes information loss, via a maximum likelihood approach. Heuristic methods are nice, because they work.…”
Section: A K-anonymization Algorithmmentioning
confidence: 99%
“…Hay et al [7] considered such an adversary and proposed a method that produces at least k candidate answers to any structural queries, namely k-candidate anonymity. Zou et al [18] further observed that an adversary can perform different structural queries to re-identify a specific person.…”
Section: Related Workmentioning
confidence: 99%
“…In order to achieve the anonymization of social network data, nodes and edges in the social network can be modified, added, deleted, or clustered. Several methods have been proposed to preserve the privacy of social networks in the past [6], [7], [9], [13], [15], [17], [18]. However, most of them considered only structural information [7], [9], [17], [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All attributes are available in plaintext to the OSN service providers and, depending on the configurations, some of them are available to third parties. It is not surprising that a subset of the profile attributes can already identify a user, even after anonymization [4,6]. Therefore, it is an interesting task to design a solution for users to: (1) protect their private profile attributes; (2) establish friendship with strangers based on their profile similarities (this is the main reason why users want to publish their profiles).…”
Section: Introductionmentioning
confidence: 99%